Smart Techno Parenting for Early Childhood Socio-Emotional Development in the Digital Age - Suargani, Ganjar; Surya, Julia; Maullasari, Sri (GENIUS: Indonesian Journal of Early Childhood Education, 2023)
Today, people live in the digital age. Everyone from all walks of life, including early childhood, is familiar with gadgets. Gadgets can hurt early childhood due to parents' lack of awareness of the dangers posed. This article elaborates on parenting strategies for early childhood socio-emotional development in the digital era. The primary sources used are national and international journals, while secondary sources are books related to the topic of discussion. Journals and books used as references discuss parenting strategies that focus on early childhood socio-emotional development in the digital age. The results show that intelligent techno parenting is an appropriate strategy to educate and develop children's potential optimally; parents should be more active and creative and understand the development of technology as a positive educational tool for children.